Studi literatur: Efektivitas pemberian ekstrak kayu manis terhadap kadar glukosa darah pada penderita diabetes mellitus tipe II - Praty Milindasari; Juniah Juniah (Holistik Jurnal Kesehatan, 2022)
Effect of cinnamon extract on blood glucose level in patients with type II diabetes mellitus:  A literature reviewBackground: The increase in cases of type II diabetes mellitus is currently quite concerning. Type II diabetes mellitus undergoes an event of uncontrolled insulin resistance, glucose. In addition to the price of drugs that tend to be expensive, diabetes drugs are currently still not fully provide solutions for people with diabetes mellitus, which makes people start to switch to other alternatives. Herbal medicine is currently very rapid among the community.Purpose:  To review the effectiveness of cinnamon extract to blood glucose levels in patients with type II diabetes mellitus.Method: Literature review is conducted based on issues, methodologies, and equations of results. The research used amounted to 5 using experimental quasi design. Searches for article data sources are conducted through the Perpusnas e-resources database, and Google scholar to retrieve relevant articles.Results: The effect of cinnamon extract in patients with diabetes mellitus got a total of 178 participants with type II diabetes mellitus obtained cinnamon extract effective in reducing blood glucose levels.Conclusion: Patients with type II diabetes mellitus aged 36-66 years old are the effective ageKeywords : Diabetes mellitus type II; Cinnamon; Blood Glucose Level. Pendahuluan: Peningkatan pada kasus diabetes mellitus tipe II saat ini cukup memprihatinkan. Diabetes mellitus tipe II mengalami peristiwa resistensi insulin, glukosa yang tidak terkontrol. Selain harga obat yang cenderung mahal, obat-obat diabetes saat ini masih belum sepenuhnya memberi solusi bagi penderita diabetes mellitus, hal tersebut yang membuat masyarakat mulai beralih ke alternatif lain. Pengobatan herbal saat ini sangat pesat di kalangan masyarakat.Tujuan: Untuk mereview efektifitas pemberian ekstrak kayu manis terhadap kadar glukosa darah pada penderita diabetes mellitus tipe II.Metode: Literature review dilakukan berdasarkan issue, metodologi, dan persamaan hasil. Penelitian yang digunakan berjumlah 5 dengan menggunakan design quasi eksperiment. Pencarian sumber data artikel dilakukan melalui database e-resources Perpusnas, dan Google scholar untuk mengambil artikel yang relevan.Hasil: Pengaruh pemberian ekstrak kayu manis pada penderita diabetes mellitus dengan total partisipan sebanyak 178 didapatkan ekstrak kayu manis efektif dalam penurunan kadar glukosa darah.Simpulan: Penderita diabetes mellitus tipe II rentang usia 36 - 66 tahun merupakan usia yang efektif